Development Map of “Aghjabadi Bakery” - Yusifov, Sadig (ADA University, 2020)
As the world is developing continuously, in parallel to this development the demands and requirements of consumers are also change and becomes complicated from day to day. To keep up with these developments, companies also need to amplify incessantly and apply all tangible and intangible innovations to the their businesses. Within this consulting project, you will be able to analyze the current situation of a recently built bakery in Aghjabadi region and get informed about its organizational, operational, and financial situation. You will also be informed about the bakery market in the region and be acquainted with the customer purchasing behavior and options. Here we will show our proposals on the way of solving the structural problems, diversifying the product ranges, and applying stimulant strategies for the short-term and long-term development of business.
Keywords: Business; Aghjabadi region -- Development.; Development of business.; Consumer satisfaction.